The moonshine women - Anderson, Michelle Collins (John Scognamiglio Books, Kensington Publishing Corp., 2026)
Every batch of Strong moonshine has its own special flavor, thanks to the secret ingredients that matriarch Lidy Strong adds to the barrels of fermenting corn mash. Whether a bucketful of golden peaches, a ripe melon or juicy, jewel-toned berries, that extra "something something" is what makes the Strong "shine" so prized--and allows the family to survive after crop prices plummeted in the wake of the Great War. Each of the Strong sisters, too, is distinct. Stoic, steadfast Rebecca would rather be with her beloved farm animals or off hunting in the woods than socializing. Middle sister Elsie is kindhearted, beautiful--and itching for a life more thrilling than the farm can offer. Jace, the youngest, is known far and wide as "Shine," a name that suits her fiery personality and flaming red hair as much as her innate skill with a still. Their father, Hiram, has been drowning himself in grief and liquor ever since his wife died. But the moonshine business is unforgiving, especially with Prohibition agents turning up in every creek and holler. When tragedy strikes, it falls to the Strong women to keep the still running, the family together, and hope burning on the horizon. From the Ozark mountains edged in oak and pine, to the outlaw paradise of Hot Springs, Arkansas--where gangsters like Al Capone line the bar at the Southern Club--the sisters' quests for vengeance, healing, and love will drive them forward, in search of a future as transformative and powerful as the purest Strong moonshine. --Provided by Publisher.